Intralayer/Interlayer Codoping Stabilizes Polarity Modulation in 2D Semiconductors for Scalable Electronics - Guitian Qiu; Lingan Kong; Mengjiao Han; Qian Zhang; Majeed Ur Rehman; Jianxian Yi; Lede Xian; Xiankai Lin; Aumber Abbas; Jiwei Chen; Yingjie Luo; Wenbo Li; et al. (Advanced Science)
Abstract 2D semiconductors show promise as a competitive candidate for developing future integrated circuits due to their immunity to short‐channel effects and high carrier mobility at atomic layer thicknesses. The inherent defects and Fermi level pinning effect lead to n‐type transport characteristics in most 2D semiconductors, while unstable and unsustainable p‐type doping by various strategies hinders their application in many areas, such as complementary metal‐oxide‐semiconductor (CMOS) devices. In this study, an intralayer/interlayer codoping strategy is introduced that stabilizes p‐type doping in 2D semiconductors. By incorporating oppositely charged ions (F and Li) with the intralayer/interlayer of 2D semiconductors, remarkable p‐type doping in WSe2 and MoTe2 with air stability up to 9 months is achieved. Notably, the hole mobility presents a 100‐fold enhancement (0.7 to 92 cm2 V−1 s−1) with the codoping procedure. Structural and elemental characterizations, combined with theoretical calculations validate the codoping mechanism. Moreover, a CMOS inverter and more complex logic functions such as NOR and XNOR, as well as large‐area device arrays are demonstrated to showcase its applications and scalability. These findings suggest that stable and straightforward intralayer/interlayer codoping strategy with charge‐space synergy holds the key to unlocking the potential of 2D semiconductors in complex and scalable device applications.